Pengaruh Pemberian Teknik Slow Deep Breathing terhadap Penurunan Kecemasaan pada Saat Pemasangan Alat Kontrasepsi di TPMB Sudarmi Tajinan - Zetiana Putri Finisha; Rani Safitri; Raden Maria (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Anxiety is frequently felt by individuals prior to contraceptive insertion because of concerns related to medical procedures. The purpose of this research was to assess the impact of a slow deep breathing method on alleviating anxiety during the contraceptive insertion process. A quasi-experimental design featuring a single group with pretest and posttest evaluations was utilized, involving 30 participants. The Hamilton Anxiety Rating Scale (HARS) was employed to evaluate anxiety levels before and after the intervention. The Wilcoxon Signed Rank Test was applied for data analysis. The findings indicated that prior to the intervention, a majority of participants experienced mild anxiety (56. 7%) and moderate anxiety (43. 3%). Following the intervention, the majority reported no anxiety (80. 0%) and 20. 0% reported mild anxiety. Analysis of the statistics indicated p = 0. 000 (p < 0.05), which signifies a substantial effect of slow deep breathing on lowering anxiety levels during contraceptive insertion. In summary, slow deep breathing serves as an efficient non-medical relaxation method for mitigating anxiety among family planning acceptors prior to the insertion of contraceptives and can be integrated into midwifery practices.